Pilanuk Dance: Forms of Existence and Moral Values "‹"‹in the Kanayatn Dayak Community - Oktariani, Dwi (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
A traditional dance work departs from a value that is owned by an ethnic group. Pilanuk dance is a dance originating from the Kanayatn Dayak tribe in West Borneo. This study discusses the existence o the Pilanuk dance which has succeeded in regenerating it amoung the Kanayatn Dayak community and the wider community. The description o the moral values contained in the Pilanuk dance o the Kanayatn Dayak tribe in West Borneo is based on the philosophy o the Pilanuk dance, the origins of creation, the practice process, and what can be seen from the Pilanuk dance form. Descriptive method to present data in the form o words obtained in the field together with a search of study documentation, and sources who are performers of the Pilanuk dance. This research was conducted in Ambawang district, Kubu raya, West Borneo. The approach taken to obtain data in this study is to use a semiotic and etnochoreologic approach. The results of the study show that the Pilanuk dance contains moral values that are beneficial to people"™s lives. Moral values can be seen from the form of motion and the philosophy on which the Pilanuk dance is created. The moral values in Pilanuk dance include dexterity, ingenuity, vigilance, seriousness, dicipline, entertainment and aestethic, responsibility, cooperation, mutual cooperation, harmony, brotherhood, friendship, the value of truth and the value of honesty.